Integrasi Nilai Islam dalam Kurikulum Pendidikan Kedokteran - Nurlaili Susanti; Riskiyah Riskiyah (Journal of Islamic Medicine, 2022)
Background: Medical education has a strategic role in producing professional doctors who will provide quality health services to the community. A medical education curriculum that integrates Islamic content is needed to strengthen professionalism as a Muslim doctor. Objective: This study examines the implementation of Islamic integration in several Islamic Medical Faculties in Indonesia. Methods: This research is qualitative research with a phenomenological approach. The research subject was taken by purposive sampling. The research subjects are the Faculty of Medicine under the State Islamic Religious College (PTKIN). Data collection techniques were carried out through document studies and interviews. Results: Each Faculty of Medicine has the concept of implementing Islamic integration in medical education with different approaches and ways. Conclusion: The implementation of the integration of Islam in medical science is reflected in curriculum development, learning activities, and assessments Keyword :Medical education, muslim doctor, Islamic value, integration, curriculum.